Derechos humanos y exportación legal de armas: Estados Unidos y Alemania frente a la crisis mexicana - Pérez Ricart, Carlos A.; Lindsay-Poland, John (El Colegio de México A.C., 2019)
This paper examines how Germany and the United States have altered their laws and policies for the control of Small Arms and Light Weapons (SALW) exports to Mexico, a country currently experiencing a severe human rights crisis. Based on interviews carried out in Germany and the United States, and official reports and secondary materials, the paper identifies that while Germany has withdrawn SALW exports to Mexico, US companies continue to export them with practically no restrictions. The text offers contributions to two academic debates: the study of the participation of non-state actors in the decision-making process on arms export policies, and the examination of how international norms affect the behavior and practices of nation states, a key issue in the constructivist agenda of International Relations.